2014
DOI: 10.1016/j.radonc.2014.11.011
|View full text |Cite|
|
Sign up to set email alerts
|

HPV16 DNA status is a strong prognosticator of loco-regional control after postoperative radiochemotherapy of locally advanced oropharyngeal carcinoma: Results from a multicentre explorative study of the German Cancer Consortium Radiation Oncology Group (DKTK-ROG)

Abstract: HPV16 DNA status appears to be a strong prognosticator of loco-regional tumour control after postoperative cisplatin-based radiochemotherapy of locally advanced oropharyngeal carcinoma and is now being explored in a prospective validation trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 41 publications
6
143
0
1
Order By: Relevance
“…HPV-positive tumors are more radio(chemo) sensitive than HPV-negative tumors (7,8) and locoregional control after PORT-C was achieved in our analysis in virtually all patients with HPV16 DNA-positive tumors (6). In contrast, in patients with HPV16 DNA-negative tumors locoregional control rates of approximately 80% were reached, implying that the HPV16 DNA infection status is not suitable as a sole biomarker for the prediction of locoregional tumor recurrences in these patients.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…HPV-positive tumors are more radio(chemo) sensitive than HPV-negative tumors (7,8) and locoregional control after PORT-C was achieved in our analysis in virtually all patients with HPV16 DNA-positive tumors (6). In contrast, in patients with HPV16 DNA-negative tumors locoregional control rates of approximately 80% were reached, implying that the HPV16 DNA infection status is not suitable as a sole biomarker for the prediction of locoregional tumor recurrences in these patients.…”
Section: Introductionmentioning
confidence: 61%
“…Previously, we and others have shown that the HPV infection status is a strong prognosticator for locoregional control in patients with locally advanced HNSCC who received postoperative radio(chemo)therapy (6,28,29) with an improved locoregional control and radiosensitivity of HPV16 DNA positive in comparison with HPV16 DNA-negative tumors. In our previous multicenter evaluation, we found virtually no recurrences in the HPV16 DNA-positive group among high-risk HNSCC patients who received PORT-C (6).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations